Key Plant, Key Pests: Sycamore (Platanus spp.) - Matthew Borden; Kelly Laplante; Juanita Popenoe; Adam Dale; Caroline R. Warwick; Brian Pearson (EDIS)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists, and landscape professionals to help identify common pests associated with regional flora. This new 6-page publication of the UF/IFAS Environmental Horticulture Department helps identify the most common pests found on trees in the sycamore group, Platanus spp., and it provides information and general management recommendations for sycamore lace bug, bacterial leaf scorch, powdery mildew, anthracnose, and canker stain. Written by Matthew Borden, Kelly Laplante, Juanita Popenoe, Adam Dale, Caroline R. Warwick, and Brian Pearson. https://edis.ifas.ufl.edu/ep601